What spelling errors can tell us about the development of processes involved in children’s spelling - Niolaki, Georgia Z.; Negoita, Alexandra; Vousden, Janet I.; Terzopoulos, Aris R.; Taylor, Laura; Masterson, Jackie (Frontiers in Psychology, 2023)
Introduction Spelling is an essential foundation for reading and writing. However, many children leave school with spelling difficulties. By understanding the processes children use when they spell, we can intervene with appropriate instruction tailored to their needs. Methods Our study aimed to identify key processes (lexical-semantic and phonological) by using a spelling assessment that distinguishes different printed letter strings/word types (regular and irregular words, and pseudowords). Misspellings in the test from 641 pupils in Reception Year to Year 6 were scored using alternatives to binary correct versus incorrect scoring systems. The measures looked at phonological plausibility, phoneme representations and letter distance. These have been used successfully in the past but not with a spelling test that distinguishes irregularly spelled words from regular words and pseudowords. Results The findings suggest that children in primary school rely on both lexical-semantic and phonological processes to spell all types of letter string, but this varies depending on the level of spelling experience (younger Foundation/Key stage 1 and older Key stage 2). Although children in younger year groups seemed to rely more on phonics, based on the strongest correlation coefficients for all word types, with further spelling experience, lexical processes seemed to be more evident, depending on the type of word examined. Discussion The findings have implications for the way we teach and assess spelling and could prove to be valuable for educators.